Modified silica gel as well as preparation method and application thereof
By modifying specific groups on the surface of the silicone, the problem of difficult removal of metal impurities in the cycloolefin copolymer is solved, and efficient and environmentally friendly metal impurities removal is achieved, improving the purity and transparency of the product.
Patent Information
- Application Number
- CN202510205094.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to efficiently remove metal impurities from cycloolefin copolymers, resulting in high ash content, degradation of dielectric properties and optical properties of the product.
Modified silica gel is prepared by modifying specific groups on the surface of the silica gel. The modified silica gel has good adsorption properties and can remove metal impurities in the cycloolefin copolymer in environmentally friendly, convenient and efficient manner.
The efficient removal of metal impurities in the cycloolefin copolymer is achieved, the Al content is reduced to 1.3-15.2ppm, and the Zr content is <1ppm, which improves the high purity and transparency of the product.
Smart Images

Figure BDA0005284275510000021 
Figure BDA0005284275510000031 
Figure BDA0005284275510000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solution polymerization post-treatment, and specifically relates to a modified silica gel and a preparation method and application thereof. Background Art
[0002] Cyclic olefin copolymer (COC) is a type of non-crystalline polymer formed by the copolymerization of cyclic olefins and α-olefins. It has excellent properties such as high transparency, low birefringence, high glass transition temperature, high chemical resistance, high dimensional stability, and low water absorption. It has been used in medical equipment, optical lenses, and food packaging. If the metallocene catalyst and its co-catalyst used in the COC production process are not treated after polymerization, they will remain in the polymer, resulting in high ash content in the product. The residual ash will affect the dielectric properties of the product, and the residual metal components will catalyze the oxidative degradation of the molecular chain at high temperature, causing yellowing and a decrease in the optical properties of the product. Therefore, removing the residual catalyst is an important guarantee for the high purity, high transparency and low dielectric constant of COC.
[0003] JPH06100668A discloses a method for purifying cycloolefin copolymers, using an aqueous solution of organic acid or inorganic acid to extract a polymer solution to remove metal impurities, but the method produces a large amount of acidic wastewater, and has requirements for acid corrosion resistance for equipment and pipelines. JPH04161421A discloses a method for removing catalysts, using water or alcohol to precipitate catalysts, and then removing catalysts by centrifugation or filtering, but the method has high requirements for filtration accuracy, and separation is difficult when the solution solid content is high. JP6050951B2 discloses a method for refining a polymer solution, using inorganic adsorbents such as molecular sieves, silica gel and aluminum oxide to adsorb metal impurities, but the impurity removal efficiency of the method is not high.
[0004] Therefore, there is an urgent need to design a new material to efficiently remove metal impurities from cycloolefin copolymers. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a modified silica gel and a preparation method and application thereof. The present invention modifies specific groups on the surface of the silica gel so that the obtained modified silica gel has good adsorption properties, which can remove metal impurities in cycloolefin copolymers in an environmentally friendly, convenient and efficient manner.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a modified silica gel, wherein the matrix of the modified silica gel is silica gel, and the surface of the silica gel is modified with at least one group as shown in Formula I, Formula II or Formula III;
[0008]
[0009]
[0010] Wherein, "*" represents the connection site between the group and the silica gel, and Formula I, Formula II or Formula III is connected to the surface of the silica gel through a -Si-O-Si- chemical bond.
[0011] R 11 , R 21 , R 31 , R 41 Each is independently selected from any one of a hydrogen atom, a C1-C12 straight or branched alkyl group, a C1-C12 alkoxy group, a C6-C30 aryl group, a halogen, a mercapto group, a hydroxyl group, and an amino group.
[0012] R 22 , R 32 , R 33 Each is independently selected from C1-C12 straight chain or branched alkyl, any one of formula IV.
[0013] n is an integer selected from 1-100, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, etc.
[0014] The modified silica gel provided by the present invention is a silica gel whose surface is modified by a dicarboxylic acid functional group. The dicarboxylic acid can chelate with the metal impurities in the cycloolefin copolymer, so that the modified silica gel has good adsorption performance and can remove the metal impurities in the cycloolefin copolymer in an environmentally friendly, convenient and efficient manner.
[0015] In the present invention, the halogen may be fluorine, chlorine, bromine or iodine. The following descriptions involving the same have the same meaning.
[0016] In the present invention, the expression of Ca-Cb represents that the number of carbon atoms in the group is ab.
[0017] In the present invention, “each independently” means that when there are multiple subjects, they may be the same as or different from each other.
[0018] In the present invention, the C1-C12 straight or branched alkyl group includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, 2-ethylhexyl, n-octyl, n-heptyl, n-nonyl, n-decyl, etc.
[0019] Specific examples of the C1-C12 alkoxy group include monovalent groups obtained by connecting O to the above-mentioned linear or branched alkyl groups.
[0020] The C6-C30 aryl group includes a monocyclic aryl group and a condensed aryl group; the monocyclic aryl group means a group containing at least one phenyl group, and when containing at least two phenyl groups, the phenyl groups are connected by a single bond, including but not limited to: phenyl, biphenyl, terphenyl, quaterphenyl, etc.; the condensed aryl group means a group containing at least two aromatic rings, and the aromatic rings share two adjacent carbon atoms and are condensed to each other. Exemplary include but are not limited to: naphthyl, anthracenyl, phenanthryl, indenyl, fluorenyl and its derivatives (9,9-dimethylfluorenyl, 9,9-diethylfluorenyl, 9,9-dipropylfluorenyl, 9,9-dibutylfluorenyl, 9,9-dipentylfluorenyl, 9,9-dihexylfluorenyl, 9,9-diphenylfluorenyl, 9,9-dinaphthylfluorenyl, spirobifluorenyl, benzofluorenyl, etc.), fluoranthenyl, triphenylene, pyrenyl, perylene, It should be noted that the monocyclic aromatic groups and condensed aromatic groups connected by a single bond also belong to the scope of aromatic groups, such as phenylnaphthyl, naphthylphenyl, naphthylnaphthyl, phenylnaphthylphenyl, etc.
[0021] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0022] As a preferred technical solution, the R 11 , R 21 , R 31 , R 41 Each is independently selected from any one of a hydrogen atom, a C1-C6 (e.g., C2, C3, C4, C5) straight chain or branched alkyl group, a C1-C6 (e.g., C2, C3, C4, C5) alkoxy group, a C6-C18 (e.g., C9, C10, C12, C15, etc.) aromatic group, a halogen, a mercapto group, a hydroxyl group, and an amino group.
[0023] Preferably, the R 11 , R 21 , R 31 , R 41 Each is independently selected from a hydrogen atom or a mercapto group.
[0024] Preferably, the R 22 , R 32 , R 33 Each is independently selected from C1-C6 (eg C2, C3, C4, C5) straight chain or branched chain alkyl, any one of formula IV.
[0025] Preferably, the silica gel is in the form of spherical particles.
[0026] Preferably, the average particle size of the silica gel is 0.2-3 mm, for example, it can be 0.4 mm, 0.6 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm, etc.
[0027] Preferably, the bulk density of the silica gel is 0.45-0.65 g / cm 3 , for example, it can be 0.46 g / cm 3 , 0.48g / cm 3 , 0.5g / cm 3 , 0.52g / cm 3 , 0.54g / cm 3 , 0.56g / cm 3 、0.58g / cm 3 , 0.6g / cm 3 , 0.62g / cm 3 , 0.64g / cm 3 wait.
[0028] Preferably, the surface of the silica gel is modified with a group shown in formula I.
[0029] In a second aspect, the present invention provides a method for preparing the modified silica gel as described in the first aspect, the preparation method comprising the following steps:
[0030] (1) silica gel reacts with a vinyl silane coupling agent to obtain silica gel with a terminal vinyl group modified on the surface;
[0031] The vinyl silane coupling agent has a structure as shown in Formula V:
[0032]
[0033] Wherein, R1, R2, and R3 are each independently selected from any one of halogen, C1-C12 straight or branched alkyl, and C1-C12 alkoxy; and at least one of R1, R2, and R3 is selected from any one of halogen and C1-C12 alkoxy;
[0034] At least one -CH2- in the C1-C12 alkoxy group in R1, R2, and R3 is replaced by an oxygen atom or not;
[0035] (2) reacting the silica gel whose surface is modified with terminal vinyl groups with a mercaptosuccinic acid compound to obtain the modified silica gel;
[0036] The mercaptosuccinic acid compound has a structure as shown in Formula VI:
[0037]
[0038] Among them, R4 has the same 11 , R 21 , R 31 , R 41 Same limited scope.
[0039] In the present invention, at least one -CH2- in the C1-C12 alkoxy group is replaced by an oxygen atom or not. For example, one -CH2- in -O-CH2-CH2-CH3 is replaced by O to obtain -O-CH2-O-CH3.
[0040] The raw materials for preparing the modified silica gel provided by the present invention contain hydroxyl groups on the surface of the silica gel, which can react with a vinyl silane coupling agent to generate silica gel whose surface is modified with terminal vinyl groups. The vinyl groups react with mercaptosuccinic acid compounds to produce modified silica gel whose surface is modified with dicarboxylic acid functional groups.
[0041] When only one of R1, R2, and R3 is selected from halogen or C1-C12 alkoxy (at least one -CH2- in the C1-C12 alkoxy is replaced by an oxygen atom or not), the surface of the silica gel is modified by a group shown in formula III; when only two of R1, R2, and R3 are selected from halogen or C1-C12 alkoxy (at least one -CH2- in the C1-C12 alkoxy is replaced by an oxygen atom or not), the surface of the silica gel is modified by at least one group shown in formula II or formula III; when three of R1, R2, and R3 are all selected from halogen or C1-C12 alkoxy (at least one -CH2- in the C1-C12 alkoxy is replaced by an oxygen atom or not), the surface of the silica gel is modified by at least one group shown in formula I, formula II, or formula III.
[0042] Preferably, R1, R2, and R3 are each independently selected from any one of halogen, C1-C6 straight or branched alkyl, and C1-C6 alkoxy; and at least one of R1, R2, and R3 is selected from any one of halogen and C1-C6 alkoxy; at least one -CH2- in the C1-C6 alkoxy in R1, R2, and R3 is replaced by an oxygen atom or not.
[0043] Preferably, R1, R2, and R3 are each independently selected from methoxy or ethoxy.
[0044] Preferably, the vinyl silane coupling agent includes at least one of vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triisopropoxysilane, vinyl dimethyl chlorosilane, vinyl dimethyl ethoxysilane, vinyl methyl dichlorosilane, vinyl methyl dimethoxysilane or vinyl methyl diethoxysilane; vinyl trimethoxysilane and / or vinyl triethoxysilane are further preferred.
[0045] Preferably, the mass ratio of the silica gel to the vinyl silane coupling agent is (1.3-3):1, for example, it can be 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, etc.
[0046] Preferably, the mass ratio of the vinyl silane coupling agent to the mercaptosuccinic acid compound is (2-12):1, for example, it can be 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, etc.
[0047] Preferably, the reaction temperature in step (1) is 80-120°C, for example, it can be 82°C, 85°C, 88°C, 90°C, 92°C, 95°C, 98°C, 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, etc.
[0048] Preferably, the reaction time of step (1) is 12-36 h, for example, it can be 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 31 h, 32 h, 33 h, 34 h, 35 h, etc.
[0049] Preferably, the reaction in step (1) is carried out in an anhydrous and oxygen-free inert solvent.
[0050] Preferably, the inert solvent includes any one of benzene, toluene, xylene, tetrahydrofuran, dimethyl sulfoxide, trichlorobenzene or acetone, or a combination of at least two thereof.
[0051] Preferably, based on the mass of the silica gel as 1 g, the volume of the inert solvent is 2-6 mL, for example, 2.2 mL, 2.4 mL, 2.6 mL, 2.8 mL, 3 mL, 3.2 mL, 3.5 mL, 3.8 mL, 4 mL, 4.2 mL, 4.5 mL, 4.8 mL, 5 mL, 5.2 mL, 5.5 mL, 5.8 mL, etc.
[0052] Preferably, the silica gel is activated silica gel.
[0053] Preferably, the activation treatment method comprises: soaking the silica gel in an acid solution to obtain the activated silica gel.
[0054] Preferably, the acid solution comprises dilute hydrochloric acid or sulfuric acid solution.
[0055] Preferably, the concentration of the acid solution is 0.01-0.2 mol / L, for example, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L, 0.04 mol / L, 0.045 mol / L, 0.05 mol / L, 0.055 mol / L, 0.06 mol / L, 0.065 mol / L, 0.07 mol / L, 0.075 mol / L, 0.08 mol / L, 0.085 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, etc.
[0056] Preferably, the soaking time is 12-24 hours, for example, it can be 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, etc.
[0057] Preferably, the soaking temperature is 20-40°C, for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, etc.
[0058] Preferably, after the soaking is completed, the steps of washing and first drying are also performed in sequence.
[0059] Preferably, the first drying temperature is 70-90°C, for example, it can be 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, etc.
[0060] Preferably, the first drying time is 8-16 h, for example, it can be 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, etc.
[0061] Preferably, after the reaction in step (1) is completed, the steps of filtering, washing and second drying are further performed in sequence.
[0062] Preferably, the second drying temperature is 70-90°C, for example, it can be 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, etc.
[0063] Preferably, the second drying time is 8-16 h, for example, it can be 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, etc.
[0064] Preferably, the reaction in step (2) is carried out in an anhydrous and oxygen-free polar solvent.
[0065] Preferably, the polar solvent includes any one of dimethyl sulfoxide, tetrahydrofuran, diethyl ether or acetone, or a combination of at least two thereof, and dimethyl sulfoxide is further preferred.
[0066] Preferably, based on the mass of the silica gel whose surface is modified with terminal vinyl groups as 1 g, the volume of the polar solvent is 2-6 mL, for example, 2.2 mL, 2.4 mL, 2.6 mL, 2.8 mL, 3 mL, 3.2 mL, 3.5 mL, 3.8 mL, 4 mL, 4.2 mL, 4.5 mL, 4.8 mL, 5 mL, 5.2 mL, 5.5 mL, 5.8 mL, etc.
[0067] Preferably, the reaction in step (2) is carried out in the presence of a photoinitiator.
[0068] Preferably, the photoinitiator comprises benzoin dimethyl ether.
[0069] Preferably, the mass ratio of the photoinitiator to the mercaptosuccinic acid compound is (0.001-0.05):1, for example, it can be 0.0015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, etc.
[0070] Preferably, the reaction in step (2) is carried out under ultraviolet light with a wavelength of 250-400nm, for example, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, etc.
[0071] Preferably, the reaction temperature in step (2) is 15-25°C, for example, it can be 15.5°C, 16°C, 16.5°C, 17°C, 17.5°C, 18°C, 18.5°C, 19°C, 19.5°C, 20°C, 20.5°C, 21°C, 21.5°C, 22°C, 22.5°C, 23°C, 23.5°C, 24°C, 24.5°C, etc.
[0072] Preferably, the reaction time of step (2) is 30-60 min, for example, it can be 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min, etc.
[0073] Preferably, after the reaction in step (2) is completed, the steps of filtering, washing and third drying are also performed in sequence.
[0074] Preferably, the temperature of the third drying is 70-90°C, for example, it can be 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, etc.
[0075] Preferably, the third drying time is 8-16 h, for example, it can be 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, etc.
[0076] In a third aspect, the present invention provides a use of the modified silica gel as described in the first aspect, wherein the modified silica gel is used for adsorbing materials.
[0077] In a fourth aspect, the present invention provides a method for removing metal impurities from a cycloolefin copolymer, the method comprising:
[0078] The modified silica gel as described in the first aspect is used to remove metal impurities in the cycloolefin copolymer by adsorption.
[0079] Preferably, the metal impurities include at least one of Ti, Zr or Al. The metal impurities are usually present in the cyclic olefin copolymer in the form of metal ions.
[0080] Preferably, the adsorption is carried out in a cycloolefin copolymer solution; the cycloolefin copolymer solution is a solution obtained by solution polymerization of cycloolefin and α-olefin.
[0081] Preferably, the cyclic olefin copolymer comprises ethylene-norbornene copolymer.
[0082] Preferably, the weight average molecular weight of the ethylene-norbornene copolymer is 50,000-100,000 g / mol, for example, 55,000 g / mol, 60,000 g / mol, 65,000 g / mol, 70,000 g / mol, 75,000 g / mol, 80,000 g / mol, 85,000 g / mol, 90,000 g / mol, 95,000 g / mol, etc.
[0083] Preferably, the PDI of the ethylene-norbornene copolymer is 2-2.5, for example, it may be 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, etc.
[0084] Preferably, the Tg of the ethylene-norbornene copolymer is 80-160°C, for example, it may be 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, etc.
[0085] Preferably, the solvent in the cycloolefin copolymer solution includes at least one of toluene, xylene, n-hexane, cyclohexane or methylcyclohexane.
[0086] Preferably, the mass percentage of cycloolefin copolymer in the cycloolefin copolymer solution is 8-30%, for example, it can be 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% and the like.
[0087] Preferably, based on the mass of the cycloolefin copolymer solution being 100%, the mass of the modified silica gel is 5-25%, for example, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, etc.
[0088] Preferably, the adsorption method includes intermittent adsorption or continuous adsorption.
[0089] In the present invention, the intermittent adsorption method is: mixing the cycloolefin copolymer solution with the modified silica gel, and performing the intermittent adsorption under stirring conditions; the present invention does not limit the stirring method, as long as the cycloolefin copolymer solution and the modified silica gel can be mixed evenly.
[0090] Preferably, the temperature of the intermittent adsorption is 60-150°C, for example, it can be 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, etc., and 80-120°C is more preferred.
[0091] Preferably, the intermittent adsorption time is 10-90 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, etc., and more preferably 30-60 min.
[0092] Preferably, the continuous adsorption is performed by allowing the cyclic olefin copolymer solution to flow through a filler column filled with the modified silica gel.
[0093] Preferably, the flow rate of the cyclic olefin copolymer solution in the continuous adsorption is 5-15 mL / min, for example, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min, 10 mL / min, 11 mL / min, 12 mL / min, 13 mL / min, 14 mL / min, etc.
[0094] Preferably, the length of the packing column is 5-150 cm (for example, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 20 cm, 30 cm, 40 cm, 50 cm, 60 cm, 70 cm, 80 cm, 90 cm, 100 cm, 110 cm, 120 cm, 130 cm, 140 cm, etc.), and the inner diameter is 15-25 mm (for example, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 21 mm, 22 mm, 23 mm, 24 mm, etc.).
[0095] Preferably, after the adsorption is completed, the method further comprises the steps of removing the solvent and a fourth drying.
[0096] Preferably, the method of removing the solvent comprises rotary evaporation.
[0097] Preferably, the fourth drying temperature is 70-90°C, for example, it can be 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, etc.
[0098] Preferably, the fourth drying time is 8-16 h, for example, it can be 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, etc.
[0099] Compared with the prior art, the present invention has the following beneficial effects:
[0100] The modified silica gel provided by the present invention has simple and easily available raw materials for preparation, has good adsorption performance, does not generate additional waste, is environmentally friendly, and can remove metal impurities in cycloolefin copolymers in an environmentally friendly, convenient and efficient manner. The Al content in the cycloolefin copolymer can be reduced to 1.3-15.2ppm, and the Zr content is less than 1ppm. DETAILED DESCRIPTION
[0101] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0102] The sources of some components in the embodiments and comparative examples are as follows:
[0103] (1)Silicone
[0104] Silica gel A: purchased from Anaiji Chemical, with an average particle size of 0.2 mm and a bulk density of 0.65 g / cm 3 ;
[0105] Silica gel B: purchased from Anaiji Chemical, with an average particle size of 0.5 mm and a bulk density of 0.62 g / cm 3 ;
[0106] Silica gel C: purchased from Qingdao Guichuang Silica Gel Desiccant Co., Ltd., with an average particle size of 1 mm and a bulk density of 0.6 g / cm 3 ;
[0107] (2) Mercaptosuccinic acid: purchased from Anaiji Chemical;
[0108] (3) Dimercaptosuccinic acid: purchased from Anaiji Chemical;
[0109] (4) Mercaptobutanediol: purchased from Anaiji Chemical.
[0110] Example 1
[0111] A modified silica gel, wherein the modified silica gel is obtained by reacting silica gel A, vinyltrimethoxysilane and mercaptosuccinic acid;
[0112] The preparation method of the modified silica gel comprises the following steps:
[0113] (1) Weigh 100 g of silica gel A, add 200 mL of 0.1 mol / L sulfuric acid solution, soak at 25° C. for 12 h, filter, rinse with deionized water three times, and vacuum dry at 80° C. for 12 h to obtain activated silica gel A;
[0114] In an anhydrous and oxygen-free environment of a glove box, 50 g of the activated silica gel A was placed in a 500 mL round-bottom flask, 200 mL of anhydrous toluene and 25 g of vinyltrimethoxysilane were added, the mixture was stirred, heated to 110° C. and refluxed, and reacted for 24 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and separated, and washed repeatedly with anhydrous methanol for three times, and then vacuum dried at 80° C. for 12 h to obtain 55.9 g of silica gel A with terminal vinyl groups modified on the surface.
[0115] (2) In a water-free and oxygen-free environment of a glove box, the silica gel A with terminal vinyl groups modified on the surface was placed in a 500 mL round-bottom flask, 200 mL of anhydrous dimethyl sulfoxide, 10 g of mercaptosuccinic acid and 0.1 g of benzoin dimethyl ether were added, and the mixture was stirred and irradiated with 365 nm ultraviolet light at room temperature for 30 min. After the reaction was completed, the silica gel was separated by filtration, washed repeatedly with anhydrous methanol, and then vacuum dried at 80° C. for 12 h to obtain 60.6 g of the modified silica gel.
[0116] Example 2
[0117] A modified silica gel, wherein the modified silica gel is obtained by reacting silica gel B, vinyltrimethoxysilane and mercaptosuccinic acid;
[0118] The preparation method of the modified silica gel comprises the following steps:
[0119] (1) Weigh 100 g of silica gel B, add 200 mL of 0.1 mol / L sulfuric acid solution, soak at 25° C. for 12 h, filter, rinse with deionized water three times, and vacuum dry at 80° C. for 12 h to obtain activated silica gel B;
[0120] In an anhydrous and oxygen-free environment of a glove box, 50 g of the activated silica gel B was placed in a 500 mL round-bottom flask, 200 mL of anhydrous toluene and 25 g of vinyltrimethoxysilane were added, the mixture was stirred, the temperature was raised to 110° C. and refluxed, and the reaction was carried out for 24 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and separated, the silica gel was taken out, and washed repeatedly with anhydrous methanol for three times, and then vacuum dried at 80° C. for 12 h to obtain 56.6 g of silica gel B with terminal vinyl groups modified on the surface.
[0121] (2) In a water-free and oxygen-free environment of a glove box, the silica gel B with the surface modified by terminal vinyl was placed in a 500 mL round-bottom flask, 200 mL of anhydrous dimethyl sulfoxide, 10 g of mercaptosuccinic acid and 0.1 g of benzoin dimethyl ether were added, and the mixture was stirred and irradiated with 365 nm ultraviolet light at room temperature for 30 min. After the reaction was completed, the silica gel was separated by filtration, repeatedly washed with anhydrous methanol, and then vacuum dried at 80° C. for 12 h to obtain 61.3 g of the modified silica gel.
[0122] Example 3
[0123] A modified silica gel, wherein the modified silica gel is obtained by reacting silica gel C, vinyl trichlorosilane and dimercaptosuccinic acid;
[0124] The preparation method of the modified silica gel comprises the following steps:
[0125] (1) Weigh 100 g of silica gel C, add 200 mL of 0.1 mol / L sulfuric acid solution, soak at 20° C. for 18 h, filter, rinse three times with deionized water, and vacuum dry at 80° C. for 12 h to obtain activated silica gel C;
[0126] In an anhydrous and oxygen-free environment of a glove box, 50 g of the activated silica gel C was placed in a 500 mL round-bottom flask, 200 mL of anhydrous toluene and 25 g of vinyltrichlorosilane were added, the mixture was stirred, the temperature was raised to 120° C. and refluxed, and the reaction was performed for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered and separated, the silica gel was taken out, and washed repeatedly with anhydrous methanol for three times, and then vacuum dried at 80° C. for 12 h to obtain 57.2 g of silica gel C with terminal vinyl groups modified on the surface.
[0127] (2) In a water-free and oxygen-free environment of a glove box, the silica gel C with the surface modified by terminal vinyl groups was placed in a 500 mL round-bottom flask, 200 mL of anhydrous dimethyl sulfoxide, 12.5 g of dimercaptosuccinic acid and 0.1 g of benzoin dimethyl ether were added, and the mixture was stirred and irradiated with 325 nm ultraviolet light at room temperature for 60 min. After the reaction was completed, the silica gel was separated by filtration, and the silica gel was taken out and repeatedly washed with anhydrous methanol, and then vacuum dried at 80° C. for 12 h to obtain 62.2 g of the modified silica gel.
[0128] Example 4
[0129] A modified silica gel, wherein the modified silica gel is obtained by reacting silica gel C, vinyl triethoxysilane and mercaptosuccinic acid;
[0130] The preparation method of the modified silica gel comprises the following steps:
[0131] (1) Weigh 100 g of silica gel C, add 200 mL of 0.1 mol / L sulfuric acid solution, soak at 20° C. for 24 h, filter, rinse with deionized water three times, and vacuum dry at 80° C. for 12 h to obtain activated silica gel C;
[0132] In an anhydrous and oxygen-free environment of a glove box, 50 g of the activated silica gel C was placed in a 500 mL round-bottom flask, 200 mL of anhydrous toluene and 17 g of vinyl triethoxysilane were added, the mixture was stirred, the temperature was raised to 80° C. and refluxed, and the reaction was carried out for 36 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered and separated, the silica gel was taken out, and washed repeatedly with anhydrous methanol for three times, and then vacuum dried to obtain 58.4 g of silica gel C with terminal vinyl modified on the surface.
[0133] (2) In a water-free and oxygen-free environment of a glove box, the silica gel C with the surface modified by terminal vinyl groups was placed in a 500 mL round-bottom flask, 200 mL of anhydrous dimethyl sulfoxide, 8.25 g of mercaptosuccinic acid and 0.1 g of benzoin dimethyl ether were added, and the mixture was stirred and irradiated with 250 nm ultraviolet light at room temperature for 45 min. After the reaction was completed, the silica gel was separated by filtration, washed repeatedly with anhydrous methanol, and then vacuum dried at 80° C. for 12 h to obtain 65.7 g of the modified silica gel.
[0134] Example 5
[0135] A modified silica gel and a preparation method thereof, which differs from Example 2 only in that the vinyltrimethoxysilane in step (1) is replaced by vinylmethyldimethoxysilane in an equal amount, and the remaining raw materials, process parameters and steps are the same as those in Example 2.
[0136] Example 6
[0137] A modified silica gel and a preparation method thereof, which differs from Example 2 only in that the vinyltrimethoxysilane in step (1) is replaced by an equal amount of vinyldimethylethoxysilane, and the remaining raw materials, process parameters and steps are the same as those in Example 2.
[0138] Example 7
[0139] A modified silica gel and a preparation method thereof, which differs from Example 1 only in that the amount of vinyltrimethoxysilane used in step (1) is 15 g, and the remaining raw materials, process parameters and steps are the same as those in Example 1.
[0140] Comparative Example 1
[0141] A modified silica gel and a preparation method thereof, which differs from Example 1 only in that the mass of mercaptosuccinic acid in step (2) is replaced by mercaptobutanediol, and the remaining raw materials, process parameters and steps are the same as those in Example 1.
[0142] Preparation Example 1
[0143] An ethylene-norbornene copolymer solution, wherein the mass percentage of the ethylene-norbornene copolymer is 17%, the mass percentage of unreacted norbornene is 13%, and the mass percentage of toluene is 70%; the Mw of the ethylene-norbornene copolymer is 64830 g / mol, the PDI is 2.38, and the Tg is 135° C. as measured by high temperature gelling agent chromatography (GPC);
[0144] The preparation method of the ethylene-norbornene copolymer solution comprises:
[0145] Under anhydrous and oxygen-free conditions, 50 g of toluene and 50 g of norbornene were placed in a three-necked flask, and a toluene solution containing 0.1 mmol of triisobutylaluminum (TIBA), 0.5 μmol of rac-ethylene bis(1-indenyl) zirconium dichloride and 6 μmol of triphenylmethyltetrakis(pentafluorophenyl)borate was added, and the mixture was stirred, heated to 90° C., 10 g of ethylene was introduced, the pressure was maintained at 0.04 MPa, and the reaction was carried out for 10 min to obtain the ethylene-norbornene copolymer solution.
[0146] Application Example 1
[0147] A method for removing metal impurities from a cycloolefin copolymer, the method comprising the following steps:
[0148] (1) 100 mL of the ethylene-norbornene copolymer solution provided in Preparation Example 1 was placed in a round-bottom flask, 5 g of the modified silica gel provided in Example 1 was added, and the mixture was stirred and adsorbed at 80° C. for 30 min;
[0149] (2) Filter the ethylene-norbornene copolymer solution, take 20 mL of the filtrate and perform rotary evaporation, and then vacuum dry at 90° C. for 12 h to obtain an ethylene-norbornene copolymer.
[0150] Application Example 2
[0151] A method for removing metal impurities from a cycloolefin copolymer, which differs from Application Example 1 only in that in step (1), an equal amount of the modified silica gel provided in Example 1 is replaced by the modified silica gel provided in Example 2, and the remaining process parameters are the same as those in Application Example 1.
[0152] Application Example 3
[0153] A method for removing metal impurities from a cycloolefin copolymer, the method comprising the following steps:
[0154] (1) The modified silica gel provided in Example 3 was loaded into a packing column with an inner diameter of 18 mm and a length of 10 cm, and 200-mesh quartz sand was loaded at a height of 2 cm at the top and bottom of the packing column;
[0155] (2) 300 mL of the ethylene-norbornene copolymer solution provided in Preparation Example 1 was placed in a round-bottom flask, and a constant flow pump was used to deliver the solution from bottom to top into the packed column at a feed rate of 10 mL / min;
[0156] (3) The final 20 mL of the filtrate was subjected to rotary evaporation and then vacuum dried at 90° C. for 12 h to obtain an ethylene-norbornene copolymer.
[0157] Application Example 4
[0158] A method for removing metal impurities from a cycloolefin copolymer, which differs from Application Example 3 only in that in step (1), an equal amount of the modified silica gel provided in Example 3 is replaced by the modified silica gel provided in Example 4, and the remaining process parameters are the same as those in Application Example 3.
[0159] Application Example 5-7
[0160] A method for removing metal impurities from a cycloolefin copolymer, which differs from Application Example 1 only in that in step (1), an equal amount of the modified silica gel provided in Example 1 is replaced by the modified silica gel provided in Examples 5-7, and the remaining process parameters are the same as those in Application Example 1.
[0161] Comparative application example 1
[0162] A method for removing metal impurities from a cycloolefin copolymer, which differs from Application Example 1 only in that in step (1), an equal amount of the modified silica gel provided in Example 1 is replaced by silica gel A, and the remaining process parameters are the same as those in Application Example 1.
[0163] Comparative Application Example 2
[0164] A method for removing metal impurities from a cycloolefin copolymer, which differs from Application Example 1 only in that in step (1), an equal amount of the modified silica gel provided in Example 1 is replaced by the modified silica gel provided in Comparative Example 1, and the remaining process parameters are the same as those in Application Example 1.
[0165] Performance Testing
[0166] The ethylene-norbornene copolymers obtained in Application Examples 1-7 and Comparative Application Examples 1-2 were tested for the content of metal impurities using inductively coupled plasma mass spectrometry (ICP-MS). The test results are shown in Table 1.
[0167] 20 mL of the ethylene-norbornene copolymer solution provided in Preparation Example 1 was subjected to rotary evaporation and then vacuum dried at 90° C. for 12 h to obtain an ethylene-norbornene copolymer. The content of metal impurities was detected by inductively coupled plasma mass spectrometry (ICP-MS) as a blank control.
[0168] Table 1
[0169] Zr content / ppm Al content / ppm Blank control 7.5 441 Application Example 1 <1 1.3 Application Example 2 <1 2.4 Application Example 3 <1 3.4 Application Example 4 <1 3.8 Application Example 5 <1 6.1 Application Example 6 <1 9.2 Application Example 7 <1 15.2 Comparative application example 1 2.35 56 Comparative Application Example 2 1.42 35
[0170] It can be seen from the test data in Table 1 that the modified silica gel provided by the present invention has good adsorption performance, and can remove metal impurities in cycloolefin copolymers in an environmentally friendly, convenient and efficient manner, and can reduce the Zr content in the cycloolefin copolymer to <1ppm and the Al content to 1.3-15.2ppm.
[0171] From the comparison of Example 2, Example 5, and Example 6, it can be seen that the more alkoxy groups the vinyl silane coupling agent contains, the easier it is to react, the more effective components are contained in the obtained modified silica gel, and the better the metal impurity removal effect. From the comparison of Example 1 and Example 7, it can be seen that the amount of vinyl silane coupling agent used is too small, the effective components in the obtained modified silica gel are less, and the metal impurity removal effect is poor.
[0172] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the modified silica gel and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified silica gel, characterized in that: The matrix of the modified silica gel is silica gel, and the surface of the silica gel is modified with at least one group shown in Formula I, Formula II or Formula III; Wherein, "*" represents the connection site between the group and the silica gel; R 11 , R 21 , R 31 , R 41 Each is independently selected from any one of a hydrogen atom, a C1-C12 straight or branched alkyl group, a C1-C12 alkoxy group, a C6-C30 aryl group, a halogen, a thiol group, a hydroxyl group, and an amino group; R 22 , R 32 , R 33 Each independently selected from C1-C12 straight or branched alkyl, any one of formula IV; n is selected from integers of 1-100.
2. The modified silica gel according to claim 1, characterized in that: The R 11 , R 21 , R 31 , R 41 Each is independently selected from any one of a hydrogen atom, a C1-C6 straight or branched alkyl group, a C1-C6 alkoxy group, a C6-C18 aryl group, a halogen, a mercapto group, a hydroxyl group, and an amino group; Preferably, the R 11 , R 21 , R 31 , R 41 are each independently selected from a hydrogen atom or a thiol group; Preferably, the R 22 , R 32 , R 33 Each is independently selected from C1-C6 straight chain or branched alkyl, any one of formula IV.
3. The modified silica gel according to claim 1, characterized in that: The silica gel is spherical particles; Preferably, the average particle size of the silica gel is 0.2-3 mm; Preferably, the bulk density of the silica gel is 0.45-0.65 g / cm 3 ; Preferably, the surface of the silica gel is modified with a group shown in formula I.
4. A method for preparing the modified silica gel according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) silica gel reacts with a vinyl silane coupling agent to obtain silica gel with a terminal vinyl group modified on the surface; The vinyl silane coupling agent has a structure as shown in Formula V: Wherein, R1, R2, and R3 are each independently selected from any one of halogen, C1-C12 straight or branched alkyl, and C1-C12 alkoxy; and at least one of R1, R2, and R3 is selected from any one of halogen and C1-C12 alkoxy; At least one -CH2- in the C1-C12 alkoxy group in R1, R2, and R3 is replaced by an oxygen atom or not; (2) reacting the silica gel whose surface is modified with terminal vinyl groups with a mercaptosuccinic acid compound to obtain the modified silica gel; The mercaptosuccinic acid compound has a structure as shown in Formula VI: Among them, R4 has the same 11 , R 21 , R 31 , R 41 Same limited scope.
5. The preparation method according to claim 4, characterized in that: The R1, R2, and R3 are each independently selected from any one of halogen, C1-C6 straight or branched alkyl, and C1-C6 alkoxy; and at least one of the R1, R2, and R3 is selected from any one of halogen and C1-C6 alkoxy; at least one -CH2- in the C1-C6 alkoxy in R1, R2, and R3 is replaced by an oxygen atom or not; Preferably, R1, R2, and R3 are each independently selected from methoxy or ethoxy; Preferably, the mass ratio of the silica gel to the vinyl silane coupling agent is (1.3-3):1; Preferably, the mass ratio of the vinyl silane coupling agent to the mercaptosuccinic acid compound is (2-12):1; Preferably, the reaction temperature in step (1) is 80-120°C; Preferably, the reaction time in step (1) is 12-36 hours; Preferably, the reaction in step (1) is carried out in an anhydrous and oxygen-free inert solvent; Preferably, the inert solvent includes any one of benzene, toluene, xylene, tetrahydrofuran, dimethyl sulfoxide, trichlorobenzene or acetone, or a combination of at least two thereof.
6. The preparation method according to claim 4, characterized in that: The silica gel is activated silica gel; Preferably, the activation treatment method comprises: soaking the silica gel in an acid solution to obtain the activated silica gel; Preferably, the acid solution comprises dilute hydrochloric acid or sulfuric acid solution; Preferably, the soaking time is 12-24 hours; Preferably, the soaking temperature is 20-40°C; Preferably, the reaction in step (2) is carried out in a polar solvent free of water and oxygen; Preferably, the polar solvent includes any one of dimethyl sulfoxide, tetrahydrofuran, diethyl ether or acetone, or a combination of at least two thereof, and dimethyl sulfoxide is further preferred; Preferably, the reaction in step (2) is carried out in the presence of a photoinitiator; Preferably, the photoinitiator comprises benzoin dimethyl ether; Preferably, the reaction in step (2) is carried out under ultraviolet light with a wavelength of 250-400 nm; Preferably, the reaction temperature in step (2) is 15-25°C; Preferably, the reaction time in step (2) is 30-60 min.
7. An application of the modified silica gel according to any one of claims 1 to 3, characterized in that: The modified silica gel is used for adsorption materials.
8. A method for removing metal impurities from a cycloolefin copolymer, characterized in that: The method comprises: The modified silica gel as described in any one of claims 1 to 3 is used to remove metal impurities in the cycloolefin copolymer by adsorption.
9. The method for removing metal impurities from a cyclic olefin copolymer according to claim 8, characterized in that: The metal impurities include at least one of Ti, Zr or Al; Preferably, the adsorption is carried out in a cycloolefin copolymer solution; the cycloolefin copolymer solution is a solution obtained by solution polymerization of cycloolefin and α-olefin; Preferably, the cyclic olefin copolymer comprises ethylene-norbornene copolymer; Preferably, the weight average molecular weight of the ethylene-norbornene copolymer is 50000-100000 g / mol; Preferably, the PDI of the ethylene-norbornene copolymer is 2-2.5; Preferably, the Tg of the ethylene-norbornene copolymer is 80-160°C; Preferably, the solvent in the cycloolefin copolymer solution includes at least one of toluene, xylene, n-hexane, cyclohexane or methylcyclohexane.
10. The method for removing metal impurities from a cyclic olefin copolymer according to claim 9, characterized in that: The mass percentage of cycloolefin copolymer in the cycloolefin copolymer solution is 8-30%; Preferably, based on the mass of the cycloolefin copolymer solution being 100%, the mass of the modified silica gel is 5-25%; Preferably, the adsorption method includes intermittent adsorption or continuous adsorption; Preferably, the intermittent adsorption temperature is 60-150°C, more preferably 80-120°C; Preferably, the intermittent adsorption time is 10-90 min, more preferably 30-60 min; Preferably, the continuous adsorption is performed by allowing the cyclic olefin copolymer solution to flow through a packing column filled with the modified silica gel; Preferably, the flow rate of the cyclic olefin copolymer solution in the continuous adsorption is 5-15 mL / min; Preferably, the packing column has a length of 5-150 cm and an inner diameter of 15-25 mm.
Citation Information
Patent Citations
Method for purifying polymer solution
JP6050951B2